PENGARUH MEDIA VIDEO TERHADAP KETERAMPILAN MENYIMAK TEKS BERITA SISWA KELAS VIII SMP NEGERI 4 KAHU - Nurfadilla; Muh Safar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to (1) describe the listening skills of news texts before using video media in Class VIII students of SMP Negeri 4 Kahu; (2) Describe the listening skills of news texts after using video media in Class VIII students of SMP Negeri 4 Kahu; (3) prove the significant influence of the use of video media on the listening skills of Class VIII students of SMP Negeri 4 Kahu. The type of research used is quantitative research using a Pre-Experimental model. The design in this study uses one group pretest-posttest. The population in this study were all 70 Class VIII students of SMP Negeri 4 Kahu. The sampling technique was simple random sampling using 23 students from each Class VIII.The results of this study indicate that: 1) The listening skills of Class VIII students of SMP Negeri 4 Kahu before using video media were in the less skilled category with an average score of Class VIII A (65), Class VIII B (69), and Class VIII C (65); 2) The listening skills of Class VIII students in news texts after using video media are in the skilled category with an average score in Class VIII A of (86), Class VIII B of (81), and Class VIII C (81); 3) There is an effect of the use of video media on the listening skills of news texts in Class VIII students of SMP Negeri 4 Kahu, which shows that HO is rejected and H1 is accepted.